Productivity and costs of Beller-Buncher and forest processor in stands of eucalypts in first cut - Simoes, Danilo [UNESP]; Fenner, Paulo Torres [UNESP]; Tsutsui Esperancini, Maura Seiko [UNESP] (Centro Pesquisas Florestais, Ufsm, 2014)
The rationalization of forest harvesting and minimization costs is a constant search by the managers involved in this process, making them decide practices which are economically viable to optimize that operation. This study aimed to evaluate technically and economically the performance of feller-buncher and the forest processor in stands of eucalypts in first cut. The technique analysis included time and movements, productivity, efficiency operational and mechanical availability. The economic analysis included the parameters operational cost, harvesting cost and energy consumption. Aiming the optimization the cost of forest harvesting, the system composed by feller-buncher and processor forest presented itself as a technically and economically viable alternative to harvesting eucalypt in first cut or stands that do not have bifurcated trees.
Produtividade e custos do Feller-Buncher e processador florestal em povoamento de eucalipto de primeiro corte
Keywords: forest harvest; process optimization; time and movements